Social integration of the older thalassaemic patient. Issue 9 (September 1990) - Politis, C; Di Palma, A; Fisfis, M; Giasanti, A; Richardson, S C; Vullo, C; Masera, G
Abstract : Because social policy favours the fullest possible social integration of chronically ill patients, we have evaluated the facilities that are needed to achieve this for patients with beta thalassaemia major in the light of the therapeutic advances that now permit them to survive into adulthood. We have investigated the social integration of adolescent and young adult thalassaemic patients, 171 from Greece and 112 from Ferrara in Italy. Patients in both areas show a good level of social integration and favourable self image, indicating what may be achieved by providing psychosocial support as part of a comprehensive approach to treatment.